factored form: y=2(x-6)(x-3) to vertex form

Thank you for giving me this golden opportunity to help you with your question!

the possible solution to this question is;

y=2((2-6)(x-3))

y=2(2x-6-6x+18)

y=2(2x-6x-6+18)

y=2(-4x+12)

y=2(12-4x)

y=24-8x

or

y=2(-2x^2+12)

y=-4x^2+24

y=24-4x^2

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up